The Cultural Life Setting of the Proverbs : - Pilch, John J. (Book collections on Project MUSE., 2016)
Reading the Proverbs as timeless observations and recommendations regarding human nature, valid for all cultures and places, blunts their cultural relevance, argues John J. Pilch. Similar in approach and format to the Social-Science Commentary on the New Testament volumes that he authored with Richard L. Rohrbaugh and Bruce J. Malina, this volume explores and describes the cultural matrix of the Mediterranean world from which the Proverbs come and of which they are descriptive. A list of social-science scenarios provides ready reference to particular aspects of the larger Mediterranean culture.